2022
DOI: 10.3390/rs14184506
|View full text |Cite
|
Sign up to set email alerts
|

What Are Contemporary Mexican Conifers Telling Us? A Perspective Offered from Tree Rings Linked to Climate and the NDVI along a Spatial Gradient

Abstract: Forest structure and composition have changed rapidly worldwide, presenting tendencies towards an increasing proportion of younger trees. From chronologies of tree-ring indices (TRI) and the reconstruction of the basal area increment (BAI), a dendroecological study was conducted from the perspective of the radial growth of twelve contemporary conifer species in a highly diverse region of the planet. From an elevational perspective, the TRI were associated with climate and the NDVI, while the BAI was also model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The signal-to-noise ratios of all three elevation chronologies were high, and were enhanced for elevations between 14.664 and 33.645. This demonstrates that the availability of climate information contained in the larch tree ring variation increased with the elevation, as did the quality (Pompa-García et al, 2022). The overall representativeness of the three samples from high to low elevation were 0.971, 0.950, and 0.936, all of which are greater than 0.85.…”
Section: Tree Growthmentioning
confidence: 82%
See 1 more Smart Citation
“…The signal-to-noise ratios of all three elevation chronologies were high, and were enhanced for elevations between 14.664 and 33.645. This demonstrates that the availability of climate information contained in the larch tree ring variation increased with the elevation, as did the quality (Pompa-García et al, 2022). The overall representativeness of the three samples from high to low elevation were 0.971, 0.950, and 0.936, all of which are greater than 0.85.…”
Section: Tree Growthmentioning
confidence: 82%
“…However, the relationship between tree rings and NDVI is very different due to the differences in local conditions. For example, Pompa-García et al (2022) found that the relationship between the tree ring chronology of Mexican coniferous species and NDVI did not vary with altitude, however, differences were observed for latitudes changing from south to north, and the relationship gradually weakened toward the north. But Wen et al (2022) found that the correlation between the tree ring width of Picea schrenkiana and NDVI in the Tianshan Mountains decreased with increasing altitude, with gradually decreasing trend from the west to east in longitude.…”
mentioning
confidence: 99%
“…The combined effect of rainfall and high temperatures at the beginning of the growing season may stress trees through the negative impact of elevated evapotranspiration rates [50,51]. The effects of increased temperatures with severe precipitation deficits have caused forest dieback and tree mortality due to high transpiration rates and hydraulic failure [1].…”
Section: Discussionmentioning
confidence: 99%
“…Treering parameters have been widely used in both small-scale climate response studies and large-scale reconstruction studies for their various advantages, including their ability to yield accurate date information, their high continuity and temporal resolution, their wide availability, and the ease with which several copies of tree rings can be obtained [8,9]. The main advantages of NDVI data on the basis of remote sensing satellite data are the ease with which these data can be acquired, their wide coverage, and their temporal resolution, which permits vegetation growth to be detected over larger areas [10][11][12]. However, the collection of remote sensing vegetation index data has a short history.…”
Section: Introductionmentioning
confidence: 99%